Penguatan Kader Kesehatan Masyarakat untuk Meningkatkan Pemanfaatan Antenatal Care pada Ibu Hamil: Studi Kuasi-Eksperimen: Strengthening Community Health Cadres to Improve Antenatal Care Utilization among Pregnant Women: A Quasi-Experimental Study - Putri, Diana; Andriani, Aida (Chakra Brahmanda Lentera Institute, 2026)
delayed detection of pregnancy-related risks. Community health cadres play a strategic role in promoting maternal health; however, their capacity to encourage regular ANC visits is often limited due to inadequate knowledge and skills. Strengthening the role of health cadres is therefore essential to improve maternal health service utilization. This study employed a quasi-experimental design with a pretest–posttest approach without a control group. The participants were 25 active community health cadres in the working area of Mandiangin Public Health Center, Bukittinggi City. The intervention consisted of structured health education and mentoring sessions focusing on ANC standards, danger signs during pregnancy, and cadres' roles in motivating pregnant women to attend ANC visits. Data on cadres' knowledge and roles were collected using structured questionnaires before and after the intervention. Data analysis was conducted using descriptive statistics and the Wilcoxon signed-rank test. The results demonstrated a significant improvement in cadres' knowledge regarding ANC, with mean scores increasing from 60.4 ± 12.3 (pretest) to 82.6 ± 8.7 (posttest) (p < 0.001). The proportion of cadres with good knowledge category increased from 32% to 88% after the intervention. Similarly, cadres' role performance showed significant improvement, with median scores rising from 28.0 (IQR: 24.0–31.0) to 36.0 (IQR: 34.0–38.0) (p < 0.001). The proportion of cadres demonstrating good role performance increased from 48% to 84%. The findings indicate that educational and mentoring-based interventions are effective in enhancing cadres' capacity to support maternal health programs at the community level. Strengthening the role of community health cadres through continuous education and mentoring can serve as an effective strategy to improve ANC utilization. Integrating cadre empowerment programs into routine public health center activities is recommended to support sustainable improvements in maternal and child health services.